The Impacts of Multiple Taxation and Para-Fiscality on Financial Performance of Small and Medium Enterprises in Tanzania - Allen Emmanuel Mrindoko (Rescollacom (Research Collaborations Community), 2026)
Small and Medium Enterprises (SMEs) are the backbone of economies globally, contributing considerably to employment, economic growth, and poverty reduction. However, SMEs face high failure rates due to limited access to finance, complex regulatory environment, low level of managerial and business skills, multiple taxation and para-fiscal taxes. Therefore, this study intends to assess the impact of multiple taxation and para-fiscality on the financial performance of SMEs in Tanzania. The study is guided by theoretical underpinning of Ability to Pay and Institutional Theories. The research was conducted in Arusha, Dodoma and Dar es Salaam Regions. The study adopted a descriptive research design and concurrent mixed-methods approach. The target population was all owners/managers of registered SMEs. The sample size was 368 SMEs owners/managers, who were selected proportionate random sampling technique. Also, trade and investment officers of selected regions, and managers of TCCIA in respective regions were purposively selected as key informants. Data were collected through structured questionnaires, interview guide, and documentary analysis Qualitative data was analysed using thematic analysis, while analysis of quantitative data was carried out using descriptive statistics and inferential statistics based on regression model. The study found that SMEs are highly exposed to multiple taxations and para-fiscal charges to a greater extent and that this situation have detrimental influence on SMEs operations. Moreover, this study found that both multiple taxation and para-fiscality have negative and statistically significant impact on financial performance of SMEs in the study areas. The study concluded that imposition of multiple taxes and para-fiscal charges results into complex and costly compliance procedures and tax burden on SMEs, which eventually shrink SME financial performance. Thus, the study recommended that the TRA establish tax incentives and revisit tax rates and simplify tax compliance rules for SMEs so as to foster SME profitability.